Broadening Horizons 3rd Conference of Young Researchers Working in the Ancient Near East - Borrell Tena, Ferran (Congressos, 2012)
Broadening Horizons is a series of international congresses dedicated to researchers, including postgraduate students, in the early-stages of their careers who are involved in a number of different disciplinary areas in the study of the Ancient Near East and the Eastern Mediterranean. The general aim of the conferences is to encourage discussion of new topics and to promote the exchange of ideas, data and scientific information among students and scholars of many different specialties archaeology, prehistory, history, anthropology, archaeobiology and philology throughout the geographical area known as the Ancient Near East. The 3rd of these congresses was held in Barcelona (Spain), from the 19th to the 21st of July 2010 in the Universitat Autònoma de Barcelona, following previous congresses which had taken place at Ghent University (Belgium) in 2006 and at Université Lyon 2 (France) in 2007. This volume includes not only the very interesting and diverse set of papers presented in Barcelona but also the invited contributions of the key speakers. These two sections are followed by a final paper by the editors about the trajectory of the BH conferences and about the particularities and difficulties confronting young scholars who are doing research in the Near East.